Linked open data for memory institutions : implementation handbook : YEAH! project deliverable no: 3 - Runardotter, Mari; Aas, Kuldar; Djupdahl, Mattias; Eiríksdóttir, Helga Jóna; Geber, Magnus; Jonsson, Östen; Lepa, Sven; Ruusalepp, Raivo; Sigurðsson, Njörður (Luleå tekniska universitet, Innovation och Design, 2014)
This report is telling the tale of three archives that collaborated in the YEAH! project to learn how to make use of the Linked Open Data (LOD). The six sections of the report first describe the main concepts of Open Data and Linked Open Data and the business case for using these in memory institutions. This is followed by a recommendation for a six-stage process for making a cultural heritage collection available as linked open data. The report does not describe the entire LOD project planning and execution cycle in memory institutions, because these projects will serve different purposes in different institutions and will be built around different use cases. Instead, the handbook presents the core activities that every project will have to undertake, split into six stages that build on one another yet allow for iterations in the process. Each workflow stage is described as a task-list that can be checked off at the end of the stage, and supported with references to tools and additional information sources.The YEAH! project, funded by three Nordic and Baltic countries to collaboratively enhance access to public information, is a cooperation project between the National Archives in Iceland, Sweden and Estonia, Luleå University of Technology and Estonian Business Archives. Godkänd; 2014; 20140506 (marrun)